PENGGUNAAN LEARNING MANAGEMENT SYSTEM (LMS) DI PERGURUAN TINGGI: STUDI KASUS DI UNIVERSITAS PENDIDIKAN INDONESIA - Munir Munir (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Factors Affecting the Use of the Learning Management System inUniversities (A Case Study in Indonesia University of Education). The purpose ofthis paper is to find out factors that affect the usage of the Learning ManagementSystem (LMS) in in Indonesia University of Education. Indonesia University ofEducation has been built LMS to support learning processes. The focus is on factorsaffecting the use of LMS in supporting effective and efficient learning processes. Inthis research the writer used Technology Acceptance Model (TAM) to find outthose factors. The data were collected using the survey technique and wereanalyzed by means of the multivariate statistic method. The result of this researchconcluded that the factors of Perceived Usefulness (PU), Perceived Ease of Use(PEOU), Intention to Use (ITU), Actual Usage Behavior (AUB) significantly affectedthe effective and efficient use of LMS in supporting learning processes.Keywords: Learning Management System (LMS), Technology Acceptance Model(TAM), Information and Communication technology (ICT).